Proceedings of the ACM SIGPLAN 2000 Conference on Programming Language Design and Implementation 2000
DOI: 10.1145/349299.349303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamo

Abstract: We describe the design and implementation of Dynamo, a software dynamic optimization system that is capable of transparently improving the performance of a native instruction stream as it executes on the processor. The input native instruction stream to Dynamo can be dynamically generated (by a JIT for example), or it can come from the execution of a statically compiled native binary. This paper evaluates the Dynamo system in the latter, more challenging situation, in order to emphasize the limits, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…MAMBO-X64 uses a variant of the Next Executing Tail (NET) scheme [13] from Dynamo [3] to generate traces. NET works by adding an execution counter to basic blocks which are the target of a backwards branch or an exit from an existing trace, which is incremented every time the basic block is executed.…”
Section: Return-aware Trace Generationmentioning
confidence: 99%
“…MAMBO-X64 uses a variant of the Next Executing Tail (NET) scheme [13] from Dynamo [3] to generate traces. NET works by adding an execution counter to basic blocks which are the target of a backwards branch or an exit from an existing trace, which is incremented every time the basic block is executed.…”
Section: Return-aware Trace Generationmentioning
confidence: 99%
“…Load and store instructions in both AArch32 and AArch64 support a similar set of addressing modes 3 , of which a few examples are shown in Table 3. Despite their similarity however, simply translating the AArch32 addressing modes into their AArch64 equivalent will not always produce correct results.…”
Section: Speculative Address Generationmentioning
confidence: 99%
“…• Previous research in Dynamo [3] has shown that effective trace generation in a DBT can improve runtime performance compared to native execution.…”
Section: Overall Performancementioning
confidence: 99%
“…Machine code to machine code JIT translation has been used to speed up execution in the Dynamo system (Bala et al, 2000). It is not used to insert additional monitoring code into the generated code.…”
Section: Related Workmentioning
confidence: 99%